The experience of losing a loved one to sudden death - Lee, Khuan; Amat, Salleh (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction: Losing someone u love is very painful. This is particularly true when the death is sudden and unexpected. Grieving is a natural process through which many people experience loss using their own resources. People who lose their loved ones to sudden death seek counseling frequently as they feel stuck in their grief. Objectives: The purpose of this study is to explore the experience of clients who had lost their loved ones to sudden death. Methods: An interpretive hermeneutic phenomenology research approach was chosen for this study. This method allows the researcher to describe a phenomenon as it was experienced and attempts to provide an understanding of the internal meaning of a client’s experience in a lived world. Results: Themes which emerged from the interviews ere the respondents’ feeling of sadness manifested in an urge to cry out. Subsequently, they found sudden death to be an unacceptable fact. Guilt and self-blame embraced them for not being able to prevent the death from happening. The respondents experienced role disruption which resulted in poor job performance and were unable to continue healthy relationships with their loved ones. At the same time, they discovered that they did not really get over the grief but had merely thought backwards and lived forward in order to achieve psychological equilibrium. Lastly, the respondents perceived personal growth when they embraced the concept of frailty of human life and improved their relationship with others. Conclusion: The experience of death, loss and grief triggers an awareness that meaning of life is not something that people can directly search for and obtain. The implication of this study is that psychosocial components play an important role in influencing a client’s health.